Neutronic effects of rhenium, gadolinia and uranium dioxide addition to a tungsten based fast spectrum space reactor. (May 2015) - Webb, Jonathan A.; Charit, Indrajit
Highlights: The effects of Re, Gd2 O3 and UO2 to W-based fuel matrices determined by MCNP code. Detailed analysis of W-based fuel elements based fast spectrum space reactor. The paper also includes submersion criticality scenario for such a conceptual reactor. Abstract: The neutronic effects of rhenium (Re), gadolinia (Gd2 O3 ) and uranium dioxide (UO2 ) addition to a W–60 vol.% UO2 fast spectrum fuel form were investigated relative to a prismatic reactor type using the MCNP5 Monte Carlo code with the ENDF/B-VII.1 cross-section database. The effects of rhenium addition to the cladding tubes and sleeves were studied over the range of 2–25 at.% as well as the corresponding effects on the reactor mass and control drum reactivity swing and neutron energy spectrum. The effects of rhenium addition to the tungsten matrix over the range of 1–5 at.% was also investigated. Lastly, the UO2 concentration was varied from 55 to 60 vol.% UO2 and the UO2 was mixed with Gd2 O3 at concentrations ranging from 2 to 10 mol.%. Each configuration was investigated for its effects on the control drum shut down margin both in a dry state and in a submerged state where the reactor was surrounded and flooded with fresh water. The high thermal spectrum absorption cross-section of tungsten, rhenium and gadolinium proved excellent in maintaining the reactor in a subcritical state when submerged in fresh water. However, increases in the concentration of rhenium and gadolinia to the matrix, cladding and fuel kernels were also accompanied by an increase in reactor mass. The control swing within the drums was not influenced by the material compositions; however, the increase in reactor size with varying UO2 and Gd2 O3 concentrations did prevent a large fraction of the neutron population from reaching the control drums. The decrease in neutron population with access to the reflector region containing the control drums caused a loss of reactivity swing in the drums by up to 2.8% Δ k / k (4.36).